Seismic collapse assessment of double-layer barrel vault roofs with double-layer vertical walls. Issue 13 (October 2019) - Kheirollahi, Mohammad; Abedi, Karim; Chenaghlou, Mohammad Reza
Double-layer barrel vault roofs with double-layer vertical walls are frequently used as a structural system for highly important public buildings; therefore, their seismic design needs special considerations. In this article, the seismic collapse behavior of these structures, used as a lateral load-resisting system, is evaluated by carrying out incremental dynamic analysis. For this purpose, different rise-to-span and height-to-span ratios are considered for the roofs and the walls, respectively. The structures are first designed in accordance with Iranian design codes and then they are modeled in OpenSees. The material and geometric nonlinearities are considered in the analyses, including the buckling response of the compression members. At the next stage, the models are subjected to incremental dynamic analysis and their median collapse capacities are extracted. Collapse margin ratios of various structures are finally derived, following FEMA-P695 methodology, and compared against the established acceptable limits. The obtained results show that collapse of the structures occurs mainly due to the buckling-mode failure of the roof. The collapse performance of the structures with large rise-to-span ratio of roofs and large height-to-span ratio of walls is unacceptable.